(untitled) (Research, Society and Development, 2021)
Introduction: Visceral leishmaniasis (VL) and human immunodeficiency virus (HIV) infection are public health problems, with high numbers of cases and fatality worldwide. Objective: To assess factors associated with leishmania/HIV co-infection in Brazil. Methodology: Retrospective cohort study with univariate and multivariate analysis of 28,265 individuals, notified and with confirmed diagnosis of VL, in the National System of Notifiable Diseases (SINAN), from 2007 to 2018, in Brazil. Results: Most of the co-infected individuals were young, male, non-white, living in urban areas, with up to eight years of schooling, and who entered this study as a new case. Greater chances of coinfection were observed for individuals aged from eleven to nineteen years (OR=1.74), twenty to thirty-nine years (OR=13.06) and over forty years (OR=6.96), who used N-methylglucamine antimoniate (OR=4.36), amphotericin B deoxycholate (OR=6.21) and liposomal amphotericin B (OR=1.60), who had recurrence (OR=3.99), whose cases evolved to treatment dropout (OR=2.00), and deaths from causes other than VL (OR=4.00) and transfer (OR=1.50). Lower chances of co-infection were observed in women (OR=0.80), living in rural areas (OR=0.54), who had five to six symptoms (OR=0.82). Conclusion: The results point to the need for improvement in the follow-up of individuals co-infected with VL/HIV, in order to reduce relapses, transfers and treatment abandonment. Special attention should be given to the timely diagnosis of HIV infection in individuals with VL, especially in young men living in urban areas.